2010
DOI: 10.1177/0040517510361804
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Yarn Locations on Color Properties of Polyester Automotive Upholstery Woven Fabrics after Abrasion

Abstract: Automotive upholstery fabrics have direct contacts with the human beings in the cars and they affect the comfort of the journeys. As one-quarter of the human body contacts Abstract Automobile upholstery fabrics are regularly exposed to various deformations because of their usage conditions in the cars. Abrasion, being one of these deformations, occurs by various rubbing forces such as sitting, cleaning, etc. In addition to the physical deformations occurring in the structure of fabrics, such as fiber and yarn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Akgun et al reported that compact fabric structures with high yarn crossing numbers (yarn intersections) were more resistant to the effects of abrasion. It was concluded that fiber ends which occurred on fabric surfaces after abrasion affected the surfaces in different manners regarding the compactness of woven structures (Akgun, Becerir, & Alpay, 2006;Akgun, Becerir, Alpay, Karaaslan, & Eke, 2010). The high tenacity of polyester fibers and continuous polyester yarns caused some fuzz but no pilling formation on the fabric surfaces (Akgun, Becerir, & Alpay, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Akgun et al reported that compact fabric structures with high yarn crossing numbers (yarn intersections) were more resistant to the effects of abrasion. It was concluded that fiber ends which occurred on fabric surfaces after abrasion affected the surfaces in different manners regarding the compactness of woven structures (Akgun, Becerir, & Alpay, 2006;Akgun, Becerir, Alpay, Karaaslan, & Eke, 2010). The high tenacity of polyester fibers and continuous polyester yarns caused some fuzz but no pilling formation on the fabric surfaces (Akgun, Becerir, & Alpay, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, from our review of the studies relating to automotive upholstery fabrics, it was seen that the majority of them examined the physical properties of the fabrics [58–61]. It has been only very recently that studies investigating comfort properties of automotive upholstery fabrics have begun to appear in the literature [6265].…”
Section: Introductionmentioning
confidence: 99%
“…of the effects of an increased number of abrasion cycles on color values of knitted and woven fabrics made from different fiber materials such as cotton, wool, polyester, viscose and different yarn structures in different fabric construction parameters [4][5][6][7][8][9][10][11]. Alpay et al [5] showed that fabrics with ring spun and open-end spun weft yarns differ from each other in both reflectance and color difference values, which tend to increase as the abrasion cycles increase.…”
Section: Introductionmentioning
confidence: 99%